Assessment of structure and governance of amenity trees in the premises of International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria - Owoeye, Y.T. (University of Ibadan, 2021)
Amenity trees are components of the urban forest which contribute significantly to human wellbeing and improves environmental quality. Benefits derivable from amenity trees are numerous but inadequate or lack of knowledge of the structure of the urban treescape as well as poor or no management practices like institutional framework has limited these benefits. A number of institutions has lot of trees planted within their premises. However, more often than not, those trees have become hazardous and threats over time because of undesirable features and unsuitability of such trees for the urban ecosystem as well as no provision or inadequate and ineffective governance framework for sustainable management of such urban green space. Many people also have some negative view and attitude towards trees as a result of their belief thereby making it difficult for them to embrace the practice of tree management and conservation within working and living premises.